2016
DOI: 10.1038/srep18816
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of the gorgonian endosymbiont Symbiodinium

Abstract: The study focused on finding a suitable cryoprotectant (CPA) and an optimum freezing protocol for the cryopreservation of the endosymbiotic dinoflagellates (Symbiodinium, clade G) of Junceella fragilis wherein the success of experiments is crucial to both scientific and ecology studies. A two-step freezing technique was developed. The viability of the thawed dinoflagellates was assayed using the adenosine triphosphate (ATP) bioassay for the first time and was further confirmed through the culturing of dinoflag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Several studies have used sucrose for the cryopreservation of the phytoplankton Symbiodinium (Chong et al . ) and the diatom Haslea ostrearia (Tanniou et al . ), as well as for the vitrification of the protoplast of the macroalga Porphyra yezoensis (Liu et al .…”
Section: Marine Algaementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used sucrose for the cryopreservation of the phytoplankton Symbiodinium (Chong et al . ) and the diatom Haslea ostrearia (Tanniou et al . ), as well as for the vitrification of the protoplast of the macroalga Porphyra yezoensis (Liu et al .…”
Section: Marine Algaementioning
confidence: 99%
“…Two‐step freezing is one of the most common cryopreservation techniques for marine algae, and using this technique, Chong et al . () cryopreserved Symbiodinium clade G with the CPT of 1 m methanol (MeOH) and 0.4 m sucrose. Tanniou et al .…”
Section: Marine Algaementioning
confidence: 99%
“…isolated from coral. Chong et al reported high viability when clade G was cryopreserved with 1M (4.05%, w/v) MeOH. Moreover, Symbiodinium clade B isolated from Pseudopterogorgia elisabethae was successfully cryopreserved with 20% MeOH or with 20% ethanol (Santiago‐Vázquez et al ), and Symbiodinium sp.…”
Section: Introductionmentioning
confidence: 99%
“…(Hagedorn and Spindler 2014). Chong et al (2016), Hagedorn et al (2010) and Santiago-Vázquez et al (2007) are among the few that have carried out studies on the cryopreservation of Symbiodinium sp. isolated from coral.…”
Section: Introductionmentioning
confidence: 99%
“…Dinoflagellates were cryopreserved using an optimised freezing protocol according to a previously described protocol on dinoflagellate extraction and washing59. Dinoflagellate samples were incubated with a CPA (1.0 M methanol and 0.4 M sucrose) in straws for 30 min and were placed 5-cm above liquid nitrogen (LN 2 ) for 30 min.…”
Section: Methodsmentioning
confidence: 99%